(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2016)
The Drastic method has been used to assess the potential sensitivity of the Groundwater In Lattakia basin using Arc GIS 9.2 Where the modified Drastic system has been developed by combining the land uses and its divisions with general Drastic model .As a result, final values of Drastic have been modulated into two categories "low and moderate sensitivity" It has been found that the introduction of the human criteriahas increased the potentialof the moderate sensitivity of the Groundwater. As a final result, the general content of the sensitivity map which has been establishedfor Lattakia basin, showed, the domination of low sensitivity category in the north western and the north eastern areas which has big location depths of the Groundwater and high topographic altitudes.In contrast, the moderate sensitivity category dominated in the southern areas of the study region. The latter areas which are characterized by the existence of varied human activities havelocation ofGroundwater levels close to the surface. استخدمت طريقة دراستيك لتقييم الحساسية الكامنة للمياه الجوفية في حوض اللاذقية باستخدام ArcGIS 9.2حيث تم تطوير نظام دراستيك المعدل بدمج استعمالات الأرض وتقسيماتها مع نموذج دراستيك العام,وبالمحصلة تم تنميط القيم النهائية لدراستيك في صفين اثنين (منخفض الحساسية ومعتدل) وقد تبين أن إدخال المعايير البشرية قد زاد من الكمون بالنسبة للحساسية المعتدلة للمياه الجوفية. بالنتيجة النهائية فقد أظهر المضمون العام لخارطة الحساسية التي تم إنشاؤها لحوض اللاذقية,سيطرة صف الحساسية المنخفضة في المناطق الشمالية الغربية والشمالية الشرقية التي تتمتع بأعماق توضع كبيرة للمياه الجوفية وارتفاعات طبوغرافية عالية, بينما سيطر صف الحساسية المعتدلة في الأجزاء الجنوبية من منطقة الدراسة (المنطقة السهلية) التي تتميز بانتشار نشاطات بشرية متنوعة وبأعماق توضع لمنسوب المياه الجوفية قريبة من السطح.